Public Debt and Economic Development: An Empirical Evidence from Nigeria - Ofurum, Clifford Obiyo; Fubara, Siminalayi Joseph (Advances in Social Sciences Research Journal, 2022)
This study investigates the impact of public debt on economic development in Nigeria. The objective is to empirical study the relationship between public debt and economic development in Nigeria between 1980 and 2019. Data were collected from the Central Bank of Nigeria (CBN) Statistical bulletin, and the Augmented DiDickey-FullerADF), Autoregressive Distributed Lag (ARDL), and Granger Causality were used to test the hypotheses and analyse the data. The results indicate that foreign debt servicing does not have a significant impact on Nigerian real GDP. Foreign debt servicing has a negative but insignificant impact on real GDP. In addition, the result indicates that external debt does not significantly impact unemployment. External debt servicing has no significant effect on unemployment. Given the study's findings and the importance of natural resource utilisation in the Nigerian economy, the study recommends that the private sector support the government in developing technology to facilitate natural resource exploitation to generate additional revenue to finance the government budget and reduce borrowings.